Critical Analysis of a Website: A Critique based on Critical Applied Linguistics and Critical Discourse Analysis - Rina Agustina (Journal of Education and Learning (EduLearn), 2013)
E-learning was easily found through browsing internet, which was mostly free of charge and provided various learning materials. Spellingcity.com was one of e-learning websites for teaching and learning English to learn spelling, vocabulary and writing, which offered various games and activities for young learners, 6 until 8 year old learners in particular. Having considered those constraints, this paper aimed to analyse the website from two different views: (1) critical applied linguistics  (CAL) aspects and (2) critical  discourse analysis (CDA). After analysing the website using CAL and CDA, it was found that the website was adequate for beginner, in which it provided fun learning through games as well as challenged learners’ to test their vocabulary. Despite of these strengths, there were several issues required further thinking in terms of learners’ broad knowledge, such as, some of learning materials focused on states in America. It was quite difficult for EFL learners if they did not have adequate general knowledge. Thus, the findings implied that the website could be used as a supporting learning material, which accompanied textbooks and vocabulary exercise books.